Grave as space for grace – "Come you sweet hour of death!": On seeing the beauty of aging and dying within an aesthetics of mortality and decay (human decomposition) - Louw, D. J. (Stellenbosch theological journal, 2022)
Within the ineluctable contingency of death and dying as horrifying and terrifying existential prospects, the notion of "grave" immediately corresponds with the natural facticity of human decomposition and the fear for death and dying. Decomposition is, in fact, a natural process beginning several minutes after death, with a process called autolysis, or self-digestion. From a pastoral and spiritual perspective, the following research questions surface: Could a Christian spirituality of grace and a theological aesthetics of brokenness contribute to start seeing in the loss of body physique and the exposure of life to the inevitable process of existential disintegration and eventual decay, a growth perspective (embodied spirituality) that contributes to the beautification of both living and dying? Rather than a nihilistic approach, it is argued that in a Christian meta-physics of resurrection hope, an eschatological approach discovers in decay, aging and deterioration, a "more" than dust-of-death-perspective. An aesthetics of immortality implies a "spirituality of more" transcending the death and funeral formula of "ashes for ashes, dust to dust". It even surpasses an epistemology of empirical seeing and observational reasoning reducing human embodiment to the decomposition of a mortifying body, lying under the ground: "Stinking like a rotting carcass, and consumed by maggots and worms" (Martin Luther). According to Paul’s argument in 1 Corinthians 15:37-38, the natural body (psychikon), and the so called "soulless corpse", are in fact not to be reduced to organic processes of decomposition. In an aesthetics of mortality, human embodiment is about a spiritual process of pneumatic germination bodies (pneumatikon). Perhaps, the reason why J. S Bach wrote a cantata with the challenging title "Come you sweet hour of death".